2016
DOI: 10.1002/pd.4914
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and limitations of prenatal screening for Prader–Willi syndrome

Abstract: This review the status of genetic laboratory testing in Prader-Willi syndrome (PWS) due to different genetic subtypes, most often a paternally derived 15q11-q13 deletion, with benefits and limitations related to prenatal screening. Medical literature was searched for prenatal screening and genetic laboratory testing methods in use or under development and discussed in relationship to PWS. Genetic testing includes six established laboratory diagnostic approaches for PWS with direct application to prenatal scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 104 publications
(259 reference statements)
1
24
0
Order By: Relevance
“…PWS can now be diagnosed at a very early age or even at prenatal period benefiting from the improved molecular diagnosis techniques and increased awareness of PWS features [5,[14][15][16]. Dobrescu et al and Gold et al reported that most patients still had a delayed diagnosis because of the early signs of PWS not recognized, inappropriate molecular diagnostic methods used and lacking of expertise in some hospitals and institutions [4,17]. Early diagnosis permits early care and treatment, which may reduce the hospital stay and tube feeding duration, hence preventing growth retardation and early onset of obesity [5,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…PWS can now be diagnosed at a very early age or even at prenatal period benefiting from the improved molecular diagnosis techniques and increased awareness of PWS features [5,[14][15][16]. Dobrescu et al and Gold et al reported that most patients still had a delayed diagnosis because of the early signs of PWS not recognized, inappropriate molecular diagnostic methods used and lacking of expertise in some hospitals and institutions [4,17]. Early diagnosis permits early care and treatment, which may reduce the hospital stay and tube feeding duration, hence preventing growth retardation and early onset of obesity [5,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…This has driven a research interest in the perinatal features of PWS since early diagnosis and adequate management are crucial to prevent obesity and its medical consequences, and improve cognitive skills (Bar et al, 2017). Butler 2017 (Butler, 2017) reported that fetal growth restriction, and decreased fetal movements are the most common perinatal features. Gross et al(2015)(Gross, Rabinowitz, Gross-Tsur, Hirsch, & Eldar-Geva, 2015) confirmed similar findings on reviewing the obstetric records of 106 individuals with PWS compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…PWS can now be diagnosed at a very early age or even at prenatal period benefiting from the improved molecular diagnosis techniques and increased awareness of PWS features [5, [14][15][16]. 7 Dobrescu et al and Gold et al reported that most patients still had a late diagnosis because the early signs of PWS not recognized, inappropriate molecular tests used, lacking of expertise in some hospitals and institutions [17,18]. Early diagnosis permits early care and treatment, which may reduce the hospital stay and tube feeding duration, hence preventing growth retardation and early onset of obesity [5, [19][20][21].…”
Section: Discussionmentioning
confidence: 99%